Exploring the male fertility potential of medicinal plants from central and West African countries: A systematic review - Ismahil Adekunle Adeniyi; Olufunke Onaadepo; Daniel Owu; Ishak Abdi Jama; Augustine Oviosun; Ekom Monday Etukudo; Elna Owembabazi; Emeka Anyanwu; Patrick Maduabuch Aja; Josiah Ifie; Eric Aigbogun; Wusa Makena; et al. (Phytomedicine Plus)
Background: Male fertility related issue among couples in developing countries has continued to prevail despites the availability of variety of synthetic drug; hence, the need to develop more effective treatment with less side effects. The present study sort to explore medicinal plants with male fertility potential in Central and West (C&W) Africa countries. Method: The present study is a systematic review that included 25 randomized controlled trial studies using experimental animal models for various male fertility related issues treated with medicine plants sourced from within any of the C&W African countries. Result: Most of the included studies were conducted in Nigeria 80 % (20/25). The mechanisms through which C&W African plant extracts enhance fertility include reducing inflammatory biomarkers, modulating oxidative stress biomarkers (SOD, CAT, and GPx), and improving reproductive hormone levels (testosterone, luteinizing hormone, and follicle-stimulating hormone). Treatment with the plant extracts were associated with increased sperm count, motility, and viability, and improved histoarchitecture of the testes. However, only a few of the included studies chemical characterized the plant used for the study; ultraviolet spectrophotometry 4 % (1/25), gas chromatography-mass spectrometry 12 % (3/25), high-performance liquid chromatography 8 % (2/25), nuclear magnetic resonance 4 % (1/25), fourier transform infrared spectroscopy 4 % (1/25) Conclusion: This review highlights the promising fertility-enhancing potential of plant species used in C&W Africa, demonstrating their ability to improve male reproductive health through antioxidative, anti-inflammatory, and hormonal modulation pathways. We recommend proper chemical characterization of the included plants to help improve our understanding of their mechanism of action.